Poetry column from a contemporary critical view (Journal of the College of Basic Education, 2023)
The issue of the "poetry column" was not a recent critical issue. However, it was frequently dealt with whenThe speakers repeatedly and copied the opinions. It is not easy to research an old case withoutAvoid what happened to others. what caught me in confusion; Because the issue of the poetry column stoppedTheses among the ancients after Al-Marzouqi when he exhausted them with clarification.Those of the hadith scholars who wrote about it did not add anything new to it except for details and interpretations that are almostbe repeated or unacceptable, as I say:((In our opinion, the ancients meant by the phrase the column of poetry “what the modernists call the imagePoetics “If we wish to be specific, we may say the meanings and images upon which Abu Tammam built his poetry.A style of poetry that differs from the old style)) (1).And some of them presented the hair shaft with a new division and with an old content, such as the division of the hair shaft.According to al-Jurjani, there are three groups (formal, aesthetic, and productive) (2).Some of them compared the concept of the ancient column of poetry with the principle of a contemporary writer, which is the principle of(Save). Estofer considered that poetry is a deep experience, while the Arabs relied on a unityThe line is in the poetry and not the poetic unit in the poem, as we can extract from the concept of Estopher.for hair (3).We did not find any reason for this comparison, and there are no scientific justifications for it. Because the era of critical theorizing is atThe Arabs are completely different from the era of theory of English criticism, in addition to the wide disparity between constructingThe Arabic poem and the construction of the English poem.So we decided to indicate the first nucleus of the column of poetry in the old criticism, and that would be in chronological order.My assumption is correct. We started with the poetic comparison and followed it up in evolution, untilA critical theory that has its conditions, themes, and problems, which is the "pillar of poetry" has been established.